Keefektifan Model Pembelajaran Problem Based Learning (PBL) dengan Berbantuan Media Wordwall dan Quizizz terhadap Kemampuan Literasi Sains Siswa Kelas VI SD - Suratimah, Dwi; Indiati, Intan; Siswanto, Joko (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
The low level of students' scientific literacy is one of the educational problems in Indonesia. Although the importance of scientific literacy has been recognized by all educators, it does not mean that students' scientific literacy is well trained. The method used in this study is the mixed methods method. The use of this research method is based on several opinions, namely Creswell (2012) As a methods, mixed methods focuses on collecting analyzing and mixing both quantitative and qualitative data in a single study or series or studies. Its central premise is that the use of quantitative and qualitative approaches in combination provides a better understanding of research problems than either approach alone. As a research method, mixed methods focuses on collecting, analyzing and mixing qualitative and quantitative data in one study can provide a better understanding or answer to research problems compared to using one of them. The results of data processing obtained during the study showed an increase in children's scientific literacy skills with wordwall and quiziz learning media. In the normality test, the data was declared normally distributed if the significance value was 0.05. In the homogeneity test, the data was declared homogeneous if the significance value was 0.05. The homogeneity test on the variable of children's scientific literacy skills with wordwall and quiziz learning media also showed that the data was homogeneous. Answering the hypothesis made by the researcher, an ANOVA test was conducted to find out that the ANOVA data for scientific literacy had a Sig. (2-tiled) value of 0.000 0.005, so it can be concluded that there is a significant difference in the average. This means that there is an influence of the use of problem-based learning methods on scientific literacy using wordwall and quiziz learning media. From these results, it was found that the class that applied the problem-based learning method in improving scientific literacy in grade VI children had a significant difference with a significance value of 0.000.